The First Preparation of Azulenylzinc Reagents and Their Use in Negishi Cross-Coupling - Dubovik, Julia; Bredihhin, Aleksei (Synthesis, 2015)
The preparation of azulenylzinc reagents from the corresponding iodoazulenes is described. The synthetic utility of the obtained reagents is demonstrated by introducing functionalized aryl and sensitive heterocyclic substituents into the azulene moiety through Negishi cross-coupling.
Keywords: azulene; cross-coupling; organometallic reagents; heterocycles; zinc